Trends in Publication of Oncologic Abstracts Presented at the American Urological Association Annual Meeting: 1997–2017. Issue 4 (20th July 2022) - Shibley, W. Patrick; Hakam, Nizar; Lui, Jason; Wang, Lin; Li, Kevin D.; Low, Patrick; Bell, Alexander; Chang, Kevin; Nabavizadeh, Behnam; Amend, Gregory; Shaw, Nathan; Breyer, Benjamin N.
Abstract: Introduction: Our primary aim was to characterize eventual publication of presented American Urological Association (AUA) Annual Meeting oncology abstracts from 1997 to 2017. We hypothesized that the percentage of abstracts presented at the AUA Annual Meeting that became published peer-reviewed manuscripts increased over time. Methods: AUA Annual Meeting abstracts in "oncology" categories from 1997 to 2017 were identified. A random sample of 100 abstracts per year were assessed for publication. An abstract was considered "published" if 1) first and last author of the abstract were included on publication, 2) abstract and publication shared 1 conclusion, and 3) publication occurred from 1 year prior to the AUA Annual Meeting up to 10 years after. The search was conducted on PubMed® utilizing the MEDLINE® database. Results: Over the 20-year observation period, 2, 100 abstracts were reviewed and 56.3% were published. The number of journals in which manuscripts were published increased from 1997 to 2017 (R 2 =0.58, p <0.001), although here wasn't an increased publication rate for AUA Annual Meeting abstracts. Median time to publication was 1.1 years (IQR: 0.6–2.2). Median impact factor (IF) of publications was 3.3 (IQR 2.4–4.7). There was a decrease in median IF with longer interval to publication, from 3.6 within 1 year to 2.8 at more than 3 years (p=0.0003). Publications from multi-institutional abstracts had a higher mean IF (3.7 vs 3.1, p <0.0001). Conclusions: The majority of oncology abstracts presented at the AUA Annual Meeting are published. Despite growth in the number of journals and rise in IF among top urology journals, the rate of publication and IF were stable over time.